PENGARUH TEACHING FACTORY TERHADAP KESIAPAN KERJA DENGAN LOCUS OF CONTROL SEBAGAI VARIABEL INTERVENING PADA MAHASISWA PROGRAM STUDI PENDIDIKAN ADMINISTRASI PERKANTORAN - Fi Sabililah, Hudiya; Ibadil Maula, Farij (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
The high dynamics of the world of work, accompanied by the rising Open Unemployment Rate (TPT) in Indonesia, has driven the need to strengthen current workforce qualifications. In line with this phenomenon, this study was designed to analyze the effect of teaching factory as a practice-based learning model on the work readiness of students in the Office Administration Education Study Program, Universitas Negeri Surabaya by considering locus of control as an intervening variable. This study employed a quantitative approach with an explanatory research design. The sampling method used probability sampling through a proportionate random sampling technique, resulting in 230 respondents from the 2022 and 2023 cohorts. Data were collected using a questionnaire distributed via Google Form. Data analysis was carried out using PLS-SEM with the assistance of SmartPLS 4 version 4.0.9.9. The findings revealed a positive and significant effect of the teaching factory learning model implemented through the School Field Introduction Program (PLP) and Field Work Practice (PKL)/Independent Internship/University Internship on work readiness (H1). The analysis further showed that a positive and significant effect between teaching factory also had a significant effect on locus of control (H2). At the same time, locus of control was proven to have a positive and significant effect on work readiness (H3). Additionally, the study found an indirect effect of teaching factory on work readiness, mediated by locus of control (H4).